2019
DOI: 10.1097/gme.0000000000001350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ospemifene on genitourinary health assessed by prospective vulvar-vestibular photography and vaginal/vulvar health indices

Abstract: This guidance document is being distributed for comment purposes only. Comments and suggestions regarding this draft document should be submitted within 60 days of publication in the Federal Register of the notice announcing the availability of the draft guidance. Submit comments to Dockets Management Branch (HFA-305), Food and Drug Administration, 5630 Fishers Lane, Rm. 1061, Rockville, MD 20852. All comments should be identified with the docket number listed in the notice of availability that publishes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…A recent 12-week, randomized, double-blind, placebocontrolled phase 3 study (NCT02638337 [41]) reported the use of vulvar-vestibular photography and direct visual assessments as secondary outcomes in 631 postmenopausal women with moderate to severe vaginal dryness [55]. Women aged 40-80 years with vaginal dryness as their MBS, ≤5% superficial cells in VMI, and vaginal pH >5.0 took ospemifene or placebo [55].…”
Section: Visual Assessments and Vulvar-vestibular Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent 12-week, randomized, double-blind, placebocontrolled phase 3 study (NCT02638337 [41]) reported the use of vulvar-vestibular photography and direct visual assessments as secondary outcomes in 631 postmenopausal women with moderate to severe vaginal dryness [55]. Women aged 40-80 years with vaginal dryness as their MBS, ≤5% superficial cells in VMI, and vaginal pH >5.0 took ospemifene or placebo [55].…”
Section: Visual Assessments and Vulvar-vestibular Imagingmentioning
confidence: 99%
“…A recent 12-week, randomized, double-blind, placebocontrolled phase 3 study (NCT02638337 [41]) reported the use of vulvar-vestibular photography and direct visual assessments as secondary outcomes in 631 postmenopausal women with moderate to severe vaginal dryness [55]. Women aged 40-80 years with vaginal dryness as their MBS, ≤5% superficial cells in VMI, and vaginal pH >5.0 took ospemifene or placebo [55]. Tissue changes from baseline to 12 weeks were assessed with the Vulvar Imaging Assessment Scale (VIAS; unvalidated 4-point scale) including 9 criteria (labia majora, labia minora, clitoris size, introital tissue elasticity, introital color, introital erythema, introital moisture, urethral glans prominence, and other findings; maximum score 27) [55].…”
Section: Visual Assessments and Vulvar-vestibular Imagingmentioning
confidence: 99%
See 3 more Smart Citations